2011
DOI: 10.1889/jsid19.10.679
|View full text |Cite
|
Sign up to set email alerts
|

An integral‐imaging three‐dimensional display with wide viewing angle

Abstract: Abstract— The viewing angle and flipping areas of a conventional integral‐imaging three‐dimensional (3‐D) display were analyzed. The pitches of the elemental image and micro‐lens are identical. The more micro‐lenses used, the smaller the viewing angle becomes and the wider the flipping areas become. In this paper, an improved integral‐imaging 3‐D display is presented. The pitch of the elemental image is larger than that of the micro‐lens. The single‐viewing angles of all micro‐lenses converge and there are no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 9 publications
0
42
0
Order By: Relevance
“…2 shows the structure of the rectangular pinhole array. The more pinholes in the pinhole array used, the smaller the viewing angle becomes [8]. The viewing angle is also inversely proportional to the aperture width of the pinhole [9,10].…”
Section: Principle and Structurementioning
confidence: 99%
See 2 more Smart Citations
“…2 shows the structure of the rectangular pinhole array. The more pinholes in the pinhole array used, the smaller the viewing angle becomes [8]. The viewing angle is also inversely proportional to the aperture width of the pinhole [9,10].…”
Section: Principle and Structurementioning
confidence: 99%
“…Moreover, the II display using the pinhole array is easily in realizing a compact 3-D-2-D convertible display system [6]. A number of studies related to the viewing angle have been reported [7][8][9][10]. For a single pinhole, the viewing angle is determined by the pitch of the pinhole and the gap between the pinhole and the elemental image [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the more elemental images that are integrated, the smaller the viewing angle becomes. 13 The viewing angle of the proposed 1-DII display θ 0 can be obtained as…”
Section: Structure and Principlementioning
confidence: 99%
“…The viewing area and viewing angle of the InI monitor is mainly determined by the lens size, the number of lenses and the distance between the pixels and the lenses [10], see Figure 2. An observer looking at the InI monitor inside of the viewing area will see a 3D reconstructed image with full parallax.…”
mentioning
confidence: 99%